Global Wine Tourism: Research, Management and Marketing 2006
DOI: 10.1079/9781845931704.0153
|View full text |Cite
|
Sign up to set email alerts
|

Younger wine tourists: a study of generational differences in the cellar door experience.

Abstract: This chapter reports on research examining the perceptions and experiences of visitors to winery cellar doors in one wine region (Swan Valley) of Western Australia. It particularly focuses on the perspective of younger wine tourists who, for current purposes, are defined as those that are members of the Generation X and Generation Y cohorts; and compares their cellar-door experience and expectations with those of older wine tourists. Participants in this study included 24 mystery shoppers sent out in four grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 9 publications
1
25
0
1
Order By: Relevance
“…These are both intrinsic motives and therefore hold important implications for marketing the festival in order to attract the high-spenders. The results found for the low-spending cluster confirms the notion stated by Charters and Fountain (2006) that the younger wine tourist values the overall tourist experience and not only the quality of the wine.…”
Section: Findings and Implicationssupporting
confidence: 93%
“…These are both intrinsic motives and therefore hold important implications for marketing the festival in order to attract the high-spenders. The results found for the low-spending cluster confirms the notion stated by Charters and Fountain (2006) that the younger wine tourist values the overall tourist experience and not only the quality of the wine.…”
Section: Findings and Implicationssupporting
confidence: 93%
“…For decades now some regions, including Western Australia's Margaret River and Swan Valley have become rural icons, developing their wine and wine tourism industries and attracting many visitors in the process. Because these regions have become well-known for their wine tourism, they have also attracted the attention of many researchers (see for example, Hall et al, 2000b;Macionis and Cambourne, 1998;Charters and Ali-Knight, 2002;Shanka and Taylor, 2004;Yuan et al, 2005;Charters and Fountain, 2006;Taylor, 2006).…”
Section: Small Wine Regions In Western Australiamentioning
confidence: 99%
“…A growing body of research has explored the significance of age or generational groupings as a factor in the wine tourism experience over the past decade (Charters and Fountain, 2006;Dodd, Yuan, and Kolyesnikova, 2006;Mitchell, 2002;Nowak, Thach, and Olsen, 2006;Treloar, 2004;Treloar, Hall, and Mitchell, 2004). In relation to younger wine tourists" experience at the winery cellar door, Mitchell"s (2002) study found no significant generational differences in satisfaction.…”
Section: Generation Y Wine and Wine Tourismmentioning
confidence: 99%